2012
DOI: 10.1039/c2jm16455h
|View full text |Cite
|
Sign up to set email alerts
|

One-pot photochemical synthesis of graphene composites uniformly deposited with silver nanoparticles and their high catalytic activity towards the reduction of 2-nitroaniline

Abstract: A one-step photochemical approach was established to quickly and specifically synthesize uniformly dispersed silver nanoparticles (AgNPs) on reduced graphene oxide (rGO) nanosheets. Silver-ammonia and graphene oxide (GO) were used as precursors to enhance the coordination-based adsorption of silver cations onto the negatively charged GO surface through ligation with ammonia, which could also continuously stabilize the nucleation and growth of AgNPs. The method allowed the easy control of the coverage percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(69 citation statements)
references
References 40 publications
6
61
0
Order By: Relevance
“…Moreover, the intensity peaks of the D and G bands were enhanced in the case of AgNPs-rGO due to the surface-enhanced Raman scattering effect of AgNPs, which is about 1700% greater than that of GO [35]. + ions than AgNO 3 , leading to creation of more initial nucleation sites [17], and 2) Ag(NH 3 ) 2 OH has a higher stability than AgNO 3 and resists reduction, hindering the growth of Ag into large particles [27]. The formation mechanism of AgNPs-rGO via electrodeposition is shown in Figure 7.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the intensity peaks of the D and G bands were enhanced in the case of AgNPs-rGO due to the surface-enhanced Raman scattering effect of AgNPs, which is about 1700% greater than that of GO [35]. + ions than AgNO 3 , leading to creation of more initial nucleation sites [17], and 2) Ag(NH 3 ) 2 OH has a higher stability than AgNO 3 and resists reduction, hindering the growth of Ag into large particles [27]. The formation mechanism of AgNPs-rGO via electrodeposition is shown in Figure 7.…”
Section: Resultsmentioning
confidence: 97%
“…[17][18][19][20][21] which is desirable as this indicates versatility. Several types of nanoparticles have been electrodeposited on graphene [22; 23], but to the best of our knowledge, there are no published articles on silver nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its unique two dimensional structure and extraordinary physicochemical properties such as large surface area [25][26][27], excellent electrical conductivity and high chemical stability [28,29], graphene is considered as an ideal two dimensional carbon support for developing highly efficient catalysts [30,31]. It was reported that loading Ag nanoparticles onto graphene can not only prevent graphene sheets from restacking and expand the application areas of graphene, but also improve the catalytic performance of Ag nanoparticles owing to the strong synergistic effect between the two components [32][33][34]. Up to now, considerable attention has been paid on the synthesis of graphene oxide (GO)/Ag and reduced graphene oxide (RGO)/Ag hybrid materials.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, there is a strong synergistic interaction between Ag nanoparticles and graphene, which can greatly enhance the catalytic property of Ag nanoparticles [13]. Moreover, it is well realized that the immobilization of Ag nanoparticles on graphene surface not only provides a new way to develop novel catalytic systems but also offers prodigious opportunities toward emerging functions [14,15]. On the other hand, magnetic nanoparticles have been 4 intensively studied and show promising applications in various fields such as magnetic fluids, data storage, catalysis and magnetic resonance imaging [16][17][18].…”
Section: Introductionmentioning
confidence: 99%